SIMULASI PENANGANAN KEGAWATDARURATAN PADA ANGGOTA PATROLI KEAMANAN SEKOLAH (PKS) BINAAN POLRES TEGAL - Ita Nur Itsna; Woro Hapsari; Anisa Oktiawati (Universitas Amikom Purwokerto, 2019)
Background : The School Safety Patrol Activity (PKS) is a learning media for students to socialize in an environment outside the school, where children learn to be more sensitive to various actions that occur in the surrounding environment. The form of PKS students' participation in their school in addition to the activities that PKS routinely conducts also needs to be briefed on emergency handling because emergency events can occur anytime and anywhere including in the school environment. This simulation was carried out aimed at increasing the knowledge and skills of PKS members in handling victims of emergency cases in the environment around the school.Method :Simulations were conducted using lecture and demonstration method on: (a) primary and secondary examinations, (b) triage, (c) evacuation of victims and (d) transportation of emergency patients.Result : (1) simulation activities can increase PKS members 'knowledge and understanding in handling emergency cases, (2) enhancing PKS members' knowledge and understanding is done by delivering material, (3) not all PKS members can practice simulated actions due to time constraints. The overall service activites can be judged good by the 4 (four) components, namely: the success of the number of participants exceeds the target because many students are enthusiastic about participating in this activity, the achievement of training objectives (80%), achievement of planned material targets (80%) , and the ability of participants in mastering the material (70%).Conclution: This simulation activity can improve students' knowledge and skills in dealing with emergency conditions that can occur in the environment around the school.